Pernikahan dini: Menurut hukum negara dan islam, faktor penyebab, dan dampak - Dzaki, Nuzulatul Akmaliyah Adz (Maliki Interdisciplinary Journal, 2024)
Marriage is the sunnah of Allah for every living creature, including humans. Marriage is not only done to fulfill biological needs, but also has other meanings. Marriage is a physical and spiritual bond between two people of the opposite sex to live a household life together with the hope of having offspring in a way that is in accordance with Islamic law. Marriage is generally carried out by men and women who are ready and mature physically and psychologically, therefore the government has set an age limit for carrying out a marriage. However, lately there have been many cases of underage marriage or commonly called early marriage, because they marry at a very young age and under the provisions of government regulations. There are several factors that cause this to happen, both because of customs, economy, and others. Early marriage also has a number of risks. Then if early marriage is not allowed in state law, what about according to Islamic law? This article will discuss early marriage in Islamic and state law, the causative factors, and its impact caused.